Micro and Small Industries and the Use of Internet: Findings from Indonesian - Tambunan, Tulus Tahi Hamonangan (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2019)
This study aims to examine the development of Indonesian micro and small enterprises in the manufacturing industry (called micro and small industries/MSIs) in utilizing the internet for their businesses. By nature, this is a descriptive study, which analyses secondary data. It also reviews key literature on the use of ICT by micro, small, and medium enterprises (MSMEs) in developing countries. It shows that MSMEs, dominated by micro and small enterprises (MSEs), has been the leading player in Indonesian domestic economic activities as they accounted for more than 90 percent of all firms and contributed to more than 50 percent of gross domestic product (GDP). But, only a small fraction of these enterprises in Indonesia that utilize the internet for business, and the intensity of internet usage varies by province and type of business. This is the first macro-level studyever conducted in Indonesia on the use of the internet by MSEs across sectors based on national data from the 2016 Economic Census conducted and data on the 2016 survey on MSEs in the manufacturing industry (MSIs). Thus, the findings of this study may add new empirical evidence to the literature on the utilization of ICT by MSMEs in developing countries.